dna2bit: high performance genomic distance estimation software for microbial genome analysis - Li, Juzeng; Tian, Yuxin; Wang, Yi; Jin, Li (Frontiers in Microbiology, 2024)
dna2bit is an ultra-fast software specifically engineered for microbial genome analysis, particularly adept at calculating genome distances within metagenome and single amplified genome datasets. Distinguished from existing software such as Mash and Dashing, dna2bit employs feature hashing technique and Hamming distance to achieve enhanced speed and memory utilization, without sacrifice in the accuracy of average nucleotide identity calculations. dna2bit has promising applications in various domains such as average nucleotide identity approximation, metagenomic sequence clustering, and homology querying. dna2bit significantly boosts computational efficiency in handling large datasets including single amplified genomes, thereby facilitating a better understanding of the population heterogeneity and comparative genomics of microorganisms. dna2bit is available at https://github.com/lijuzeng/dna2bit.